2015
DOI: 10.1104/pp.114.255489
|View full text |Cite
|
Sign up to set email alerts
|

LACCASE5 Is Required for Lignification of the Brachypodium distachyon Culm

Abstract: The oxidation of monolignols is a required step for lignin polymerization and deposition in cell walls. In dicots, both peroxidases and laccases are known to participate in this process. Here, we provide evidence that laccases are also involved in the lignification of Brachypodium distachyon, a model plant for temperate grasses. Transcript quantification data as well as in situ and immunolocalization experiments demonstrated that at least two laccases (LACCASE5 and LACCASE6) are present in lignifying tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 40 publications
(56 reference statements)
4
74
0
Order By: Relevance
“…Stems of low-lignin transgenic switchgrass (Panicum virgatum) down-regulated for COMT had increased amounts of xylan, the predominant hemicellulose component in switchgrass, both when plants were cultivated in the greenhouse (Fu et al, 2011) and in the field (Baxter et al, 2014). In brachypodium (Brachypodium distachyon), the reduced lignin content of a mutant for the ligninspecific laccase BdLAC5 was compensated for by a slight increase in the content of hemicellulose, whereas the amount of cellulose remained unchanged (Wang et al, 2015b). The brown midrib mutants isolated in maize show a characteristic brown coloration of the leaf midrib that is associated with reduced lignin levels and altered lignin composition (Sattler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stems of low-lignin transgenic switchgrass (Panicum virgatum) down-regulated for COMT had increased amounts of xylan, the predominant hemicellulose component in switchgrass, both when plants were cultivated in the greenhouse (Fu et al, 2011) and in the field (Baxter et al, 2014). In brachypodium (Brachypodium distachyon), the reduced lignin content of a mutant for the ligninspecific laccase BdLAC5 was compensated for by a slight increase in the content of hemicellulose, whereas the amount of cellulose remained unchanged (Wang et al, 2015b). The brown midrib mutants isolated in maize show a characteristic brown coloration of the leaf midrib that is associated with reduced lignin levels and altered lignin composition (Sattler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In B. distachyon, BdCESA4 , 7 and 8 encode cellulose synthase A (CESA) proteins and the loss‐of‐function mutants for BdCESA4 and 7 showed a reduced amount of crystalline cellulose in the SCW (Handakumbura et al ., ). BdLAC5 , 6 and 10 are members of the laccase family and mutation in BdLAC5 leads to a reduction in the culm lignin level (Wang et al ., ). In our RNA‐seq analysis, BdLAC5 was induced by both SA and BTH, but BdLAC6 and 10 were found in the SA‐specific DEGs.…”
Section: Resultsmentioning
confidence: 97%
“…Lignin has been reported to be involved in multiple resistances, including cotton Verticillium wilt resistance (Bonello and Blodgett, 2003;Hu et al, 2018;Zhang et al, 2017). Previous studies have shown that plant laccases (LAC4, LAC11 and LAC17) are necessary and non-redundant with peroxidase for lignin polymerization in Arabidopsis (Berthet et al, 2011;Zhao et al, 2013), and that they oxidatively polymerize monolignols (p-coumaryl, coniferyl and sinapyl alcohols) into p-hydroxyphenyl (H), guaiacyl (G) and syringyl (S) lignin units (Wang et al, 2015). In this study, we isolated a lignin laccase, GhLAC15, which affected Verticillium wilt resistance by increasing total lignin and KL levels and by modifying lignin composition and structure, as well as associated cell wall traits.…”
Section: Discussionmentioning
confidence: 99%